Konflik Elit Partai Berbasis Agama dan Rekruitmen Calon Kepala Daerah di Provinsi Lampung - hawari, nadirsah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2019)
This study attempts to map the internal dynamics of several faith-based political parties in facing the Lampung governor election contest in 2018. This theme is considered important because the solidity of political parties is largely determined by the party's ability to manage existing dynamics or conflicts. In fact, sometimes Islamic parties find it difficult to be free from intrigue, conflicts of interest which lead to a pragmatic attitude in determining political decisions, especially when intersected with the axis of power. Whatever the reason, we believe that building political awareness by adopting education, recruitment and religious political awareness is precisely a recipe for the creation of strong political immunity for a political party so that the Islamic political philosophy of maintaining religious norms and managing world affairs can be realized. Preaching of the mass media about the conflicts or internal dynamics of political parties at the local level such as in the Lampung governor election in 2018 was the main focus of this research. As a result, both of PAN, PPP, PKB, and PKS are indicated to be trapped in the practice of political pragmatism in determining the support of candidates even though the four political parties are not the same in addressing and resolving any differences that occur within the party's body.